2010
DOI: 10.1002/pmic.201000261
|View full text |Cite
|
Sign up to set email alerts
|

Finding new posttranslational modifications in salivary proline‐rich proteins

Abstract: Proline-rich proteins (PRPs) are the most complex family of salivary peptides with distinct isoforms and PTMs. Up to date, only the serine phosphorylation at positions 8, 17, and 22 have been experimentally observed on acidic PRP (aPRPs), and at position 8 on basic PRP1 and 2. The presence of a glucoronyl group at Ser17 was also noticed on aPRP. The main goal of this study was to identify new PTMs and distinct isoforms of salivary PRPs using LC-MALDI-TOF/TOF. Through the salivary peptidome characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 28 publications
(35 reference statements)
1
27
1
Order By: Relevance
“…We evaluated the NetNGlyc server (89) (http://www.cbs.dtu.dk/services/NetNGlyc/), used in published studies (9093, 27) to provide a qualitative measure of the likelihood for N -linked glycosylation, given the protein sequence; however, we found that NetNGlyc predictions inconsistent with our results. Table I compares NetNGlyc predictions and site-occupancy results from proteomics data for Phil-82.…”
Section: Resultscontrasting
confidence: 64%
“…We evaluated the NetNGlyc server (89) (http://www.cbs.dtu.dk/services/NetNGlyc/), used in published studies (9093, 27) to provide a qualitative measure of the likelihood for N -linked glycosylation, given the protein sequence; however, we found that NetNGlyc predictions inconsistent with our results. Table I compares NetNGlyc predictions and site-occupancy results from proteomics data for Phil-82.…”
Section: Resultscontrasting
confidence: 64%
“…For example, secreted proteins are glycosylated through both N-and O-glycosidic bonds, and if the peptide backbone is occupied by oligosaccharides, then most likely they will not be identified in a proteomic analysis. 40,[45][46][47][70][71][72] As such, if the glycosylated protein has a low molecular mass, then the chance of being identified decreases. Therefore, the immediate consequence is false-negative data.…”
Section: Problems and Challenges Encountered In Analyzing Secretomesmentioning
confidence: 99%
“…Although this method is much better, more sensitive, and perhaps more reliable providing sequence information, there are also drawbacks associated with this method: Some proteins truncate and/or degrade, and when analyzed, this information is not taken into consideration. [45][46][47]49 As such, if a quantitation is performed, there is a high chance that the quantitation will produce false-positive or not very accurate results. [50][51][52][53][54] To compensate for that, one may have to consider the use of more than two or even three peptides for quantitation purposes.…”
Section: Bottom-up Secretomicsmentioning
confidence: 99%
See 2 more Smart Citations